Diabetic Ketoacidosis and the Use of New Hypoglycemic Groups: Real-World Evidence Utilizing the Food and Drug Administration Adverse Event Reporting System - Hilal A. Thaibah; Otilia J. F. Banji; David Banji; Thamir M. Alshammari (Pharmaceuticals)
Background: Diabetic ketoacidosis (DKA), a life-threatening complication, can occur in individuals with type 2 diabetes during illness, stress, or medication use. This study examines DKA signals in type 2 diabetes, focusing on sodium–glucose cotransporter-2 (SGLT2) inhibitors, glucagon-like peptide-1 (GLP-1) receptor agonists, and dipeptidyl-peptidase-4 (DPP-4) inhibitors. Methods: DKA reports from Q1 2019 to Q3 2024 were retrieved from the FDA Adverse Event Reporting System (FAERS). Associations between primary exposure and outcomes were ascertained using four key metrics: Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Empirical Bayes Geometric Mean (EBGM), and Information Component (IC). Results: SGLT2 inhibitors exhibited the higher DKA risk in 2019–2021 (ROR: 314.86 [95% CI 301.76–328.53], PRR of 245.69 [95% CI 235.47–256.36], IC of 6.90, and EBGM of 120), declining in 2022–2024. GLP-1 receptor agonists showed an ROR increase from 2.88 [95% CI 2.56–3.25] in 2019–2021 to 4.64 [95% CI 4.06–5.29] in 2022–2023, slightly declining to 3.95 [95% CI 3.27–4.74] in 2024. DPP-4 inhibitors exhibited a steady ROR rise from 6.81 [95% CI 5.52–8.40] in 2019–2021 to 8.57 [95% CI 6.24–11.76] in 2022–2023 and further to 11.02 [95% CI 6.71–18.10] in 2024. PRR, EBGM, and IC values followed similar trends. The age groups 41–60 and 61–91 years were the most affected, with hospitalization at its highest rate for DPP4-inhibitors in Q1–Q3 of 2024. Hospitalizations were also observed with GLP-1 receptor agonists and SGLT2 inhibitors. Life-threatening events and fatalities were also reported, with physicians contributing to most reports. Conclusions: DKA signals were observed for all three drug classes, particularly among elderly patients, highlighting the need for careful monitoring, especially during periods of illness or stress. However, the risk was higher in the SGLT2 inhibitor group than in the other groups.